Correction: Effect of ionic size compensation by Ag+ incorporation in homogeneous Fe-substituted ZnO: studies on structural, mechanical, optical, and magnetic properties. Issue 51 (16th August 2018) - Bajpai, Gaurav; Srivastava, Tulika; Patra, N.; Moirangthem, Igamcha; Jha, S. N.; Bhattacharyya, D.; Riyajuddin, Sk; Ghosh, Kaushik; Basaula, Dharma R.; Khan, Mahmud; Liu, Shun-Wei; Biring, Sajal; et al.
Abstract : Correction for 'Effect of ionic size compensation by Ag + incorporation in homogeneous Fe-substituted ZnO: studies on structural, mechanical, optical, and magnetic properties' by Gaurav Bajpai et al., RSC Adv., 2018, 8, 24355–24369.